Flexible, breathable, and highly environmental-stable Ni/PPy/PET conductive fabrics for efficient electromagnetic interference shielding and wearable textile antennas. (15th June 2021) - Liu, Qiongzhen; Yi, Cong; Chen, Jiahui; Xia, Ming; Lu, Ying; Wang, Yuedan; Liu, Xue; Li, Mufang; Liu, Ke; Wang, Dong
Abstract: Lightweight and flexible multifunctional conductive fabrics with excellent environmental stability are highly demanded for electromagnetic interference (EMI) shielding and e-textiles related applications. The relationship between the fabric structure and the EM properties of conductive fabrics has aroused extensive research interest, but it is still full of challenges. Herein, warp knitted polyethylene terephthalate (WK-PET) fabric and non-woven PET (NW-PET) fabric with irregular pore structure and similar thickness are selected as substrates. Flexible Ni/PPy/PET fabrics with high EMI shielding effectiveness have been facilely fabricated by in-situ polymerization of pyrrole (Py) and subsequent electroless plating of nickel. The conductivity, EMI shielding effectiveness and the normalized effectiveness of the Ni/PPy/NW-PET fabric is 96.32 S/cm, 77.87 dB, 1600.19 dB cm 2 /g, respectively, which are better than those of the Ni/PPy/WK-PET (91.71 S/cm, 62.6 dB, 1037.11 dB cm 2 /g). A simplified fabric structure model and fractal dimension of the fabrics have been proposed in this study to reveal the relationship between the fabric structure and the EMI shielding effectiveness. It implies that the fractal dimension of a conductive fabric is highly related to its absorption EMI shielding effectiveness. It also suggests a fabric with a higher fractal dimension as a base material can provide more connected conductive networks and better EMI shielding effects for the resulting conductive fabric. Moreover, the Ni/PPy/NW-PET fabric demonstrates outstanding heat-humid stability, high bending stability and washability, as well as great potential in wearable fabric antennas. In short, this work may provide a novel idea for the development of high-performance conductive fabrics. Highlights: The relationship between fabric structure and the EMI shielding effectiveness has been studied. A simplified fabric structure model is proposed for calculation of the theoretical conductive layer thickness. The fractal dimension of a conductive fabric is highly related to its absorption EMI shielding effectiveness. The EM properties of the Ni/PPy/NW-PET fabric prove the high environmental stability. This conductive fabric demonstrates its great potential in wearable textile antennas.